Dephasing of Exchange‐Coupled Spins in Quantum Dots for Quantum Computing. Issue 11 (12th September 2021) - Huang, Peihao
Abstract: A spin qubit in semiconductor quantum dots holds promise for quantum information processing for scalability and long coherence time. An important semiconductor qubit system is a double quantum dot trapping two electrons or holes, whose spin states encode either a singlet–triplet qubit or two single‐spin qubits coupled by exchange interaction. In this article, progress on the spin dephasing of two exchange‐coupled spins in a double quantum dot is reported. First, the schemes of two‐qubit gates and qubit encodings in gate‐defined quantum dots or donor atoms based on the exchange interaction are discussed. Then, the progress on spin dephasing of a singlet–triplet qubit or a two‐qubit gate is reported. The methods of suppressing spin dephasing are further discussed. The understanding of the spin dephasing may provide insights into the realization of high‐fidelity quantum gates for spin‐based quantum computing. Abstract : Spin qubits in quantum dots hold promise for quantum computing for scalability and long coherence time. This review and perspective article describes quantum gates and dephasing of exchange‐coupled spins in a double quantum dot, encoding a singlet–triplet qubit, or two single‐spin qubits. The method for reducing spin dephasing is discussed for applications in spin‐based quantum computing.